What research and theory inspires IA/UX, and how can this change behavior and help make a political and humanitarian difference?. Issue 1 (24th October 2017) - Busch, Joseph; Cooksey, Dave; Pass, Jeff; Pope, Ren; Surla, Stacy; Wal, Thomas Vander; Welchman, Lisa; Willis, Dan
ABSTRACT: This session is a moderated panel discussion among senior IA/UX practitioners from the greater Washington, DC area. Its goal is to challenge and inspire the ASIST research community. Among themes the panel will discuss are: 1) how research and theory inspires client project work – what types of research is needed, and what would be considered accessible and practical research; and 2) how IA/UX (including content strategy, taxonomy, governance, etc.) can change behavior, and help make a political and humanitarian difference.